Rectal paracetamol in small children with fever. Issue 6 (June 1979) - Vernon, S; Bacon, C; Weightman, D
Abstract : 37 febrile children aged between 3 months and 6 years were treated with paracetamol in a dose of 15–20 mg/kg by either oral elixir or rectal suppository. The rectal route was found to have an equal antipyretic effect and offers a practical alternative in those children for whom the oral route is not possible.20